Hybrid electric vehicles: a mini overview - Shanono, Ibrahim Haruna; Muhammad, Aisha (Penerbit UMP, 2021)
The present greenhouse effect and its arrays of limitations on energy sources have made Hybrid Electric Vehicles (HEV’s) a current research focus due to its reduced amount of fuel usage. The ability to simultaneously deliver power to the wheels from the mo-tor/engine made HEVs to have greater advantages (less fuel consumption and reduced internal combustion engine size without compromising the power output) over the tradi-tional vehicles. Despite its low patronage in markets, there is still hope that its popularity in the market will rise due to the superior qualities associated with it. This paper presented an brief review of Hybrid Electric Vehicles, by focusing on history, architecture and energy sources.